Leaders supporting leaders: Leaders' role in building resilience and psychologically healthy workplaces during the pandemic and beyond. Issue 4 (July 2022) - Grimes, Kelly; Matlow, Anne; Tholl, Bill; Dickson, Graham; Taylor, Deanne; Chan, Ming-Ka
The COVID-19 pandemic is now endemic and has taken a terrible toll on the health workforce and its leaders. Stress and burnout are rampant, and health workers are leaving in record numbers. Using data collected during the first four waves of the pandemic, and a longitudinal analysis of these data, the authors identify ongoing challenges to health leadership related to building resilience and psychologically healthy workplaces. The article is organized around three questions: What happened during Waves 1 to 4? What did we learn? And what should be done differently? Eight actions emerged around the theme of "leaders supporting leaders": build personal resilience; practice compassionate leadership; model effective interpersonal leadership behaviour; ensure frequent and authentic communication; participate in networks and communities of practice; balance short- and long-term commitments; apply systems thinking; and contribute to a collaborative, national strategy.